One-year clinical outcome of amphilimus polymer-free drug-eluting stent in diabetes mellitus patients: Insight from the ASTUTE registry (AmphilimuS iTalian mUlticenTre rEgistry). (1st July 2016) - Colombo, Antonio; Godino, Cosmo; Donahue, Michael; Testa, Luca; Chiarito, Mauro; Pavon, Anna Giulia; Colantonio, Riccardo; Cappelletti, Alberto; Monello, Alberto; Magni, Valeria; Milazzo, Diego; Parisi, Rosario; et al.
Abstract: Background: Despite several improvements in drug-eluting stent (DES) technology, patients with diabetes mellitus (DM) are affected by higher rate of adverse events after PCI with DES, mainly in terms of target lesion revascularization (TLR). The Cre8 stent, a polymer-free amphilimus-eluting stent (AES), has shown promising preliminary results in DM patients. The ASTUTE registry was conceived to assess clinical performance of this polymer-free AES in DM in a "real-world" multicenter-independent cohort of patients. Methods: 1216 consecutive patients (1637 lesions) treated with Cre8 between August 2011 and January 2015 were retrospectively enrolled and divided in two groups: DM and non-DM patients. The primary and secondary endpoints were target lesion failure (TLF) and TLR at 1-year, respectively. Results: 1-Year clinical outcome was available for 407 (80%) DM and 566 (84%) non-DM patients. Diabetic patients were more frequently affected by hypertension (p < 0.001) and dyslipidemia (p < 0.001) and more frequently dialyzed (p = 0.010). At 1-year, TLF occurred in 50 (5.1%) overall patients, and was similar in DM and non-DM patients (4.9 vs 5.3%, respectively, p = 0.788). The secondary endpoint (TLR) occurred in 3% of overall patients and similarly in DM and non-DM patients (3.7 vs 2.5%, respectively, p = 0.273). Primary and secondary endpoints were similar also between insulin and non-insulin dependent DM patients. Conclusions: The results of this large, real-world, multicenter-independent registry show that Cre8 AES has similar safety and efficacy profile in DM as well as non-DM patients, reducing the adverse outcomes related to DM in patients undergoing PCI. A large randomized trial will be necessary to definitely prove these preliminary findings.